1987
DOI: 10.1139/b87-278
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive biology of boreal forest herbs. I. Breeding systems and pollination

Abstract: Detailed observations and experimental studies of the reproductive biology of 12 boreal forest herbs were conducted over a 3-year period (1978–1980) in spruce–fir forests of central New Brunswick. The species examined were Aralia nudicaulis, Chimaphila umbellata, Clintonia borealis, Cornus canadensis, Cypripedium acaule, Linnaea borealis, Maianthemum canadense, Medeola virginiana, Oxalis montana, Pyrola secunda, Trientalis borealis, and Trillium undulatum. All taxa are insectpollinated perennials and most exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 29 publications
2
72
1
1
Order By: Relevance
“…Pollination studies have often compared seed production of plants exposed to natural pollination with those subject to pollinator exclusion or augmented pollination (33)(34)(35)(36). Herbivory studies, on their part, have frequently revealed extensive herbivory on flowers or developing fruits, a situation particularly frequent among perennial herbs such as H. foetidus (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Pollination studies have often compared seed production of plants exposed to natural pollination with those subject to pollinator exclusion or augmented pollination (33)(34)(35)(36). Herbivory studies, on their part, have frequently revealed extensive herbivory on flowers or developing fruits, a situation particularly frequent among perennial herbs such as H. foetidus (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Species that bloom in early spring when unfavourable weather conditions often prevail are susceptible to unpredictable pollinator service. Probably as a response to uncertain pollination environments many early blooming herbs possess floral traits, such as extended floral longevities and selfcompatibility, which reduce the likelihood of reproductive failure (Schemske et al, 1978;Barrett and Helenurm, 1987;Herrera, 1995). However, self-compatible species with long floral lifespans may be vulnerable to unpredictable pollinator service, which can potentially result in increased self-fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…About 40 % of the species of forest grasses of forest ecosystems of the temperate zones have autogamy [4]. But, basically, the researchers record pollination deficitinforestgrassesasoneofthekeyreasonsforthelowleveloffruiting.…”
Section: Resultsmentioning
confidence: 99%